2010
DOI: 10.1111/j.1365-2966.2010.16510.x
|View full text |Cite
|
Sign up to set email alerts
|

SAO RAS 6-m telescope spectroscopic observations of globular clusters in nearby galaxies

Abstract: We present the results of medium‐resolution spectroscopy of 28 globular clusters (GCs) in six nearby galaxies of different luminosities and morphological types, situated in M33 (15 objects), M31 (three), IC10 (four), UGCA86 (four), Holmberg IX (one) and DDO71 (one) obtained at the Special Astrophysical Observatory 6‐m telescope. Measurements of Lick absorption line indices and comparison with Simple Stellar Population models enabled us to obtain their spectroscopic ages, metallicities and α‐element to Fe abund… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 123 publications
4
36
1
Order By: Relevance
“…Similar differences have also been observed for dwarf galaxies (e.g. Beasley et al 2008;Mackey & Gilmore 2004;Sharina et al 2010) 1 . The most extreme example was found in the Fornax dSph where the stars have a broad metallicity distribution with −2.5 < [M/H] < −0.2 with a peak at [M/H] = −1.0 while the globular clusters are all metal-poor with −2.6 < [M/H] < −1.4 (Larsen et al 2012b).…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar differences have also been observed for dwarf galaxies (e.g. Beasley et al 2008;Mackey & Gilmore 2004;Sharina et al 2010) 1 . The most extreme example was found in the Fornax dSph where the stars have a broad metallicity distribution with −2.5 < [M/H] < −0.2 with a peak at [M/H] = −1.0 while the globular clusters are all metal-poor with −2.6 < [M/H] < −1.4 (Larsen et al 2012b).…”
Section: Introductionsupporting
confidence: 84%
“…Globular clusters in dwarf galaxies are in general very metalpoor, mostly even more metal-poor than the peak metallicity of the dwarf's stellar MDF (e.g. Mackey & Gilmore (2004); Sharina et al (2010)). The Fornax dSph, for example, contains four GCs with [M/H] ∼ −2.5 to -1.9 and one more metalrich GC at [M/H] ∼ −1.5 dex, whereas its stellar MDF peaks at [M/H] ∼ −1.0 with a long tail towards lower metallicities (Strader et al 2003;Helmi et al 2006;Larsen et al 2012b).…”
Section: The Mdf Of Globular Clusters In Dwarf Galaxiesmentioning
confidence: 99%
“…For U49, our metallicity determination agrees with the previous spectroscopic metallicity estimate by Brodie & Huchra (1991) within the (large) uncertainty on their measurement. For R12, our new metallicity is 0.22 dex lower than the spectroscopic estimate of [Fe/H] = −0.73 ± 0.01 of Sharina et al (2010), although the 0.01 dex uncertainty on that measurement appears somewhat optimistic (the same paper quotes an overall metallicity of [Z/H] = −0.6 ± 0.2). Our measurements generally agree with those based on the RGB slope from Sarajedini et al (1998), within the 0.1-0.3 dex uncertainties on those estimates.…”
Section: Metallicities: Comparisons With Previous Workcontrasting
confidence: 54%
“…Puzia et al (2005) finds an [α/Fe] ∼ +0.4 for their sample of extragalactic GCs. In the recent study of Sharina et al (2010) it is found that the [α/Fe] ratios of GCs tend to be higher on average for giants than for dwarf galaxies. If a gE has recently accreted nearby dwarfs with its GCs, they should have therefore lower [α/Fe] ratios than the GCs formed within the protogalaxy.…”
Section: α-Enhanced Vs Solar-scaled Tracksmentioning
confidence: 99%